1991
DOI: 10.1063/1.104902
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations up to 712 GHz in InAs/AlSb resonant-tunneling diodes

Abstract: Oscillations have been obtained at frequencies from 100 to 712 GHz in InAs/AlSb double-barrier resonant-tunneling diodes at room temperature. The measured power density at 360 GHz was 90 W cm-2, which is 50 times that generated by GaAs/AlAs diodes at essentially the same frequency. The oscillation at 712 GHz represents the highest frequency reported to date from a solid-state electronic oscillator at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
299
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 783 publications
(310 citation statements)
references
References 7 publications
3
299
2
Order By: Relevance
“…24,25 Additionally, a number of solid state diode sources have been extended to higher frequency. 26,27 Of all of the techniques, those most closely related to the fast scan submillimeter spectroscopic technique ͑FASSST͒ system described here are also based on backward wave oscillator ͑BWO͒ tubes. In 1953, Kompfner and Williams demonstrated that self-sustained oscillation in traveling wave structures could be achieved by the interaction between the oppositely directed group and phase velocities.…”
Section: B Current Spectroscopic Practice: the Source And Detector Pmentioning
confidence: 99%
“…24,25 Additionally, a number of solid state diode sources have been extended to higher frequency. 26,27 Of all of the techniques, those most closely related to the fast scan submillimeter spectroscopic technique ͑FASSST͒ system described here are also based on backward wave oscillator ͑BWO͒ tubes. In 1953, Kompfner and Williams demonstrated that self-sustained oscillation in traveling wave structures could be achieved by the interaction between the oppositely directed group and phase velocities.…”
Section: B Current Spectroscopic Practice: the Source And Detector Pmentioning
confidence: 99%
“…21,22 Despite all these desirable properties (low voltage, high PVCR and high speed), most RTDs and RITDs of the 6.1 Å family are poorly suited as photodetectors, since the staggered or even broken type-II bandgap alignment does not provide the means for sufficient accumulation of minority charge carriers at the RTS. The AlSb/GaSb double barrier RTS resembles conventional AlGaAs/GaAs RTDs and provides a well-defined type-I band alignment with large offsets in conduction and valence band.…”
mentioning
confidence: 99%
“…Resonant tunnelling diodes (RTDs) have attracted much attention owing to their wide-bandwidth negative differential resistance (NDR), up to hundreds of GHz [1]. Because RTDs can be easily integrated in electronic and optoelectronic circuits, the applications span from high frequency signal generation and high speed signal processing to millimetre-wave frequency optoelectronics [2].…”
mentioning
confidence: 99%